2013
DOI: 10.1556/oh.2013.29647
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus recurrence after liver transplantation in Hungary. Trends over the past 10 years

Abstract: Bevezetés: A hepatitis C-vírus-fertőzés kiújulása továbbra is kihívás májátültetést követően. Célkitűzés: Az elmúlt tíz évben hepatitis C-vírus-infekcióval transzplantált betegek adatainak elemzése, összevetése korábbi eredményeinkkel. Módszer: A szerzők vizsgálták a donor és recipiens perioperatív adatait, a túlélést, a szövődmények arányát a hepatitis C-vírus-infekcióval összefüggő és egyéb indikációval végzett májátültetések, valamint korai és késői hepatitis C-vírus-infekció kiújulása esetén. Eredmények: 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In HCV recurrence after LT, there is a trend toward greater recurrence rate of HCV, particularly during the first year after LT ( 24 ). Gelley et al reported that HCV recurrence was observed mainly within the first year after LT (83%), compared to 56% within 6 months and 20% within 3 months ( 25 ). However, due to the lack of clinical benefit and occurrence of side effects, there is currently no evidence to recommend prophylactic or pre-emptive HCV treatment to prevent HCV recurrence after LT ( 22 23 26 27 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In HCV recurrence after LT, there is a trend toward greater recurrence rate of HCV, particularly during the first year after LT ( 24 ). Gelley et al reported that HCV recurrence was observed mainly within the first year after LT (83%), compared to 56% within 6 months and 20% within 3 months ( 25 ). However, due to the lack of clinical benefit and occurrence of side effects, there is currently no evidence to recommend prophylactic or pre-emptive HCV treatment to prevent HCV recurrence after LT ( 22 23 26 27 28 ).…”
Section: Discussionmentioning
confidence: 99%